A practicum at Swift Foods Incorporated Purok Malinawon, Brgy. Conel General Santos City - Santos, Suzzette Marie B. (2003)
In the summer of 2002, a plant practicum was conducted at Swift Foods Inc., Purok Malinawon, Brgy. Conel, General Santos City. This aimed to give us students a hands-on experience on the actual processing of fresh dressed chicken. The student trainee was able to work on the different lines of production inside the processing plant. She was also exposed to the different stages of poultry production which includes the hatchery, the poultry farm and then finally at the poultry processing plant. Aside from learning how to properly dress a chicken, she was taught the proper way of sorting and packing fresh dressed chicken. She was to conduct Plant Line Inspections during the last part of the practicum period. She was able to apply the theories she learned in school to the actual performance of the dressing operations. She was expected to have a written output of everything she had done during the practicum. This include the lessons she learned, the problems she encountered and recommendations which she thinks could contribute to the improvement of the current practice in the dressing plant